TASAWUF KOTA - Chusnan, Masyitoh (Al Qalam, 2009)
The development of Islamic mysticism faces the neiv era cifter it is merely found at villagers. Nowadays, Islamic mysticism goes on urban society and has irifluenced the society. Due to its transcendental esoteric side, Islamic mysticism fills the empty spaces of urban modem society. Along the day, people fail to persuade their hearts and souls into the deepest level of humanity. They have framed in the modern life style which merely measured by financial, matter, luxury, and so on. Actually, it is no one and only the measure of happiness. Nowadays, more people start aware that Islamic mysticism (religion) gives them the composure and true mean of life. This life is gift from God, therefore we have to recognize ma’rifat of God. In Islamic mysticim, they fin God as source of happiness.How the religiousty of Jamaah Pengajian Pengurus Cabang Muhammadiyah (PCM) Slipi Kota Bambu, West Jakarta, by the implementation of Islamic mysticism values becomes the main question of this research.This research shows that their religiosity is significant enough. It is based on high implementation of Islamic mysticism values at Jamaah Pengajian Pengurus Cabang Muhammadryah (PCM) Slipi Kota Bambu, Jakarta Barat. In the other case, we found low implementation of Islamic mysticism values, and needed to be improved. So, this religiousily of J amaah Pengajian Pengurus Cabang Muhammadiyah (PCM) Slipi Kota Bambu, West Jakarta, by the implementation of Islamic mysticism values, can be called urban Islamic mysticism (tasawuf kota) thas has the ways to apply subtantive values (not symbolic) of islamic mysticism.